2016
DOI: 10.1007/s00442-016-3773-4
|View full text |Cite
|
Sign up to set email alerts
|

Small reductions in corolla size and pollen: ovule ratio, but no changes in flower shape in selfing populations of the North American Arabidopsis lyrata

Abstract: The shift from outcrossing to selfing is often accompanied by striking changes in floral morphology towards a "selfing syndrome", which is characterized by flowers with reduction in size, pollen: ovule (P/O) ratio, and herkogamy. This study aims to test whether such changes have occurred in the North American Arabidopsis lyrata, which is of particular interest because of the relatively recent transitions to selfing in this system. Flower size, flower shape, herkogamy levels, P/O ratio, and floral integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 59 publications
1
48
1
Order By: Relevance
“…In the short term, outcrossing in L. cavanillesii persists because of the continued attractiveness of SC flowers to pollinators, as has been suggested for mixed-mating populations of Camissoniopsis cheiranthifolia (Dart et al 2012) and Collinsia verna Vogler 2003, 2004). In this sense, the outcrossing syndrome of the SC population of L. cavanillesii may simply reflect a recent evolutionary transition to self-compatibility in part of the species' range (Foxe et al 2010;Busch et al 2011;Carleial et al 2016;, perhaps in response to selection for reproductive assurance or after a series of population bottlenecks that purged the population of its inbreeding depression (Kirkpatrick and Jarne 2000;Guo et al 2009;Foxe et al 2010). In the longer term, however, we should expect such populations to evolve increased selfing rates and ultimately a selfing syndrome (but see also Spigler and Kalisz 2017).…”
Section: Sc Plantsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the short term, outcrossing in L. cavanillesii persists because of the continued attractiveness of SC flowers to pollinators, as has been suggested for mixed-mating populations of Camissoniopsis cheiranthifolia (Dart et al 2012) and Collinsia verna Vogler 2003, 2004). In this sense, the outcrossing syndrome of the SC population of L. cavanillesii may simply reflect a recent evolutionary transition to self-compatibility in part of the species' range (Foxe et al 2010;Busch et al 2011;Carleial et al 2016;, perhaps in response to selection for reproductive assurance or after a series of population bottlenecks that purged the population of its inbreeding depression (Kirkpatrick and Jarne 2000;Guo et al 2009;Foxe et al 2010). In the longer term, however, we should expect such populations to evolve increased selfing rates and ultimately a selfing syndrome (but see also Spigler and Kalisz 2017).…”
Section: Sc Plantsmentioning
confidence: 84%
“…; Carleial et al. ; Voillemot et al. ), perhaps in response to selection for reproductive assurance or after a series of population bottlenecks that purged the population of its inbreeding depression (Kirkpatrick and Jarne ; Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Third, relative to closely related selfing taxa, the flowers of outcrossers are often larger, with larger stigmas and longer styles (Snell and Aarssen ; Sicard and Lenhard ; Duncan and Rausher ; but see Carleial et al. ). Consequently, the potential number of competing pollen grains and the distance over which their pollen tubes may compete are also greater, intensifying both gametophytic competition and selection against slow germination and pollen tube growth rate (PTGR) (Travers and Shea ).…”
Section: Consequences Of Mating System For Sexual Selectionmentioning
confidence: 99%
“…The study of mating system evolution among flowering plant taxa has revealed many instances in which suites of morphological or life-history traits have coevolved with self-fertilization: the well-known "selfing syndrome" (Darwin 1876;Ornduff 1969;Richards 1986;Sicard and Lenhard 2011). Self-fertilization has evolved independently within many families, genera, and species, and may be associated with evolutionary changes in sex allocation (Delesalle et al 2008;Delesalle and Mazer 2009;Mazer et al 2009), genetic architecture ), floral development rate or life span (Wyatt 1986;Runions and Geber 2000;Mazer et al 2004Mazer et al , 2009Dudley et al 2007;Delesalle et al 2008), physiological rates (Mazer et al 2010a;Dudley et al 2012), flower size (Ornduff 1969;Lyons and Antonovics 1991;Goodwillie et al 2006;Sicard and Lenhard 2011;Doubleday et al 2013;Tedder et al 2015;Carleial et al 2017), floral scent (Doubleday et al 2013), flower brightness (Button et al 2012), style length (Duncan and Rausher 2013), habitat preference (Anderson et al 2015;Schneider and Mazer 2016), and life history Dudley et al 2007;Shimizu and Tsuchimatsu 2015;Schneider and Mazer 2016). Few studies have investigated the effects of mating system on pollen performance (Smith-Huerta 1996; Kerwin and Smith-Huerta 2000;Taylor and Williams 2012;Hove and Mazer 2013), but it has been proposed that intrasexual selection should cause traits that affect the competitive ability of male gametophytes to diverge between outcrossing versus regularly self-pollinating taxa…”
Section: Selectionmentioning
confidence: 99%
See 1 more Smart Citation